(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article emphasizes the need to further strengthen medical control over compliance with sanitary and hygienic requirements in order to strengthen public health and prevent diseases, as well as in regions where the environmental situation is in critical condition.